The residents - Heins, Kaitlin, author; Levy, EJ, advisor; Alexander, Ruth, committee member; Becker, Leslee, committee member (Colorado State University. Libraries, 2017)
The Residents is a collage horror novel that follows Robbie, a wilderness ranger in Aspen, as she is mourns the death of her partner, Evie, and is haunted by her in their previously-shared home. Robbie's perspective on class, nature, and sexuality informs her memories of Evie and their relationship. When Evie's brother, Dylan, comes to stay with Robbie in Aspen, offering to help Robbie put the house on the market, Robbie suspects that he has other motives even as he helps her move past her grief, guilt, and rage. This story considers the damaging impact of humans on both natural and human terrain. It explores grief and culpability in respect to a dying partner and a dying planet. It uses the trope of body horror to explore self-destruction, anorexia, and sexuality.